PETER’S PSYCHOSOCIAL DEVELOPMENT IN PRODIGAL SON NOVEL BY DANIELLE STEEL - Madarita, Madarita; Natsir, M.; Asanti, Chris (Fakultas Ilmu Budaya Universitas Mulawarman, 2019)
The purpose of this research is to find out Peter’s Psychosocial Development stages in the novel Prodigal Son by Danielle Steele. The design of this research is qualitative. The data were taken from the novel itself. After the data were collected, then they were interpreted by using Erikson’s theory. Further, after being analyzed there were three stages of psychosocial development that appeared in Peter, they were, school age, young adulthood, and middle adult as the result of this research. Thus, the researcher concluded that Peter’s psychological development cannot be interpreted as a single entity, yet it is understanding as multiple psychological developments. Tujuan dari penelitian ini adalah untuk mengetahui tahapan-tahapan Perkembangan Psikososial Peter dalam novel Prodigal Son karya Danielle Steele. Desain penelitian ini adalah kualitatif. Data diambil dari novel itu sendiri. Setelah data dikumpulkan, kemudian ditafsirkan dengan menggunakan teori Erikson. Selanjutnya, setelah dianalisis ada tiga tahap perkembangan psikososial yang muncul di Peter, yaitu, usia sekolah, dewasa muda, dan dewasa menengah sebagai hasil dari penelitian ini. Dengan demikian, peneliti menyimpulkan bahwa perkembangan psikologis Peter tidak dapat diartikan sebagai entitas tunggal, namun dipahami sebagai perkembangan psikologis ganda.